2010
DOI: 10.1177/1077558710367735
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Presence of a Reported Medical Home and Emergency Department Use Among Children With Asthma

Abstract: This study examined data from the 2005-2006 National Survey of Children with Special Health Care Needs to assess the relationship among children with asthma between a reported medical home and emergency department (ED) use. The authors used 21 questions to measure 6 medical home components: personal doctor/nurse, family-centered, compassionate, culturally effective and comprehensive care, and effective care coordination. Weighted zero-inflated Poisson regression analyses assessed the independent effects of hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 38 publications
(48 reference statements)
2
29
1
Order By: Relevance
“…In the general pediatric population, parent-reported care in a medical home has been associated with increased receipt of well-child care, 7-9 decreased emergency department (ED) use, 7,8 and no differences in hospitalizations. 8 In children with chronic conditions, parent-reported care in a medical home has been associated with no differences in receipt of preventive care, 10,11 mixed results for ED visits, 10,12,13 and no differences in hospitalizations. 10 Two published studies that have examined the relationship between practice-reported PCMH measures and health care utilization by children also show mixed results.…”
Section: The Patient-centered Medical Home (Pcmh) Ismentioning
confidence: 96%
“…In the general pediatric population, parent-reported care in a medical home has been associated with increased receipt of well-child care, 7-9 decreased emergency department (ED) use, 7,8 and no differences in hospitalizations. 8 In children with chronic conditions, parent-reported care in a medical home has been associated with no differences in receipt of preventive care, 10,11 mixed results for ED visits, 10,12,13 and no differences in hospitalizations. 10 Two published studies that have examined the relationship between practice-reported PCMH measures and health care utilization by children also show mixed results.…”
Section: The Patient-centered Medical Home (Pcmh) Ismentioning
confidence: 96%
“…To demonstrate the value of community based health services for patients with asthma or of asthma self-management programs, it is of value to report healthcare resource utilization (ie, emergency room visits, hospital readmissions) as a program outcome measure. [12][13][14][15] Although the length of this asthma awareness program was relatively short, its effect on asthma knowledge was profound. Program participants realized statistically significant improved post-test scores (P Ͻ .001).…”
Section: Discussionmentioning
confidence: 99%
“…Overcrowded EDs at safety net hospitals-that is, hospitals committed to serving those with low incomes, no insurance, and who have difficulty receiving treatment elsewhere (Dewan & Sack, 2008)-are indicative of a failure of the health system to adequately serve disadvantaged communities. Increased access to primary health care services reduces use of EDs for non-emergencies (Roby et al, 2010;Wang, Villar, Mulligan, & Hansen, 2005), use of EDs for emergency treatment of chronic diseases (Diedhiou, Probst, Hardin, Martin, & Xirasagar, 2010), and overall health care costs (Guo, Wade, Pan, & Keller, 2010). Perhaps most importantly, increased primary care access improves total patient health (Hurley, Freund, & Taylor, 1989;Kasper, 1987).…”
mentioning
confidence: 99%